Detection of rhinovirus RNA in nasal epithelial cells by in situ hybridization - Bruce, Christine (J Virol Methods, 1990)
This paper describes the development and evaluation of in situ hybridization (ISH) for the detection of rhinovirus in cells obtained from nasal washings of volunteers infected with human rhinovirus 14 (HRV-14). Twenty-five (66%) and 27 (71%) of 38 volunteers inoculated with HRV-14 had evidence of infection by virus isolation and ISH, respectively, on at least one of 4 days investigated after virus challenge. In contrast, only 14 of 38 (37%) volunteers had significant antibody rises as detected by the neutralization test. Of the 38 volunteers inoculated with HRV-14, only 13 (34%) had symptoms of colds. Of these, 12 (92%) and 10 (77%) were positive by virus isolation or ISH, respectively, on at least one day. Six (46%) had significant antibody rises by neutralization. Similarly, of the 38 volunteers challenged, 22 (58%) were asymptomatic and of these 10 (45.5%) and 12 (54.5%) were positive by virus isolation and ISH, respectively, on at least one day. Only 8 (36.4%) of these asymptomatic volunteers showed significant antibody rises by neutralization. There were significant associations between the detection of rhinoviruses by ISH and virus isolation on the third day (P<0.025) after virus challenge in the group as a whole and in the symptomatic group. These results show that generally rhinovirus detection by ISH compares well with virus isolation and both tests are clearly more sensitive than the neutralization test in detecting evidence of infection. It is concluded that ISH is an interesting new technique that may play an important role in the study of rhinovirus infection and pathogenesis.